Safety climate of migrant construction workers and its relationship with their safety performance in the construction industry in Abu Dhabi, UAE - Zafar, Kamran (2023)
Objective: Safety of migrant construction workers is now becoming a global concern and this requires the identification of the important safety climate factors and attention to them to enhance the workers’ overall safety performance in this industry. Methodology: A cross-sectional study aimed to evaluate the relationship between the safety climate and its relationship with safety performance (in terms of safety participation, safety compliance, and selfreported near misses and injuries) of migrant construction workers in Abu Dhabi. 141 respondents from the major nationalities (Indians, Pakistanis, and Bangladeshi) participated in this study, from the 2 industrial zones (Abu Dhabi and Al Ain) of this emirate. Sociodemographic characteristics, information about safety climate, and safety performance were assessed by using a specifically designed questionnaire for the construction industry in English and respondents’ native languages (Hindi, Urdu, and Bengali). Descriptive statistics determined the socio-demographic and work information whereas spearman’s correlation coefficient test was carried out to determine the relationship between safety climate and safety performance of the migrant construction workers. The chisquare test was carried out to compare the safety performance among the Indian, Bangladeshi, and Pakistani migrant construction workers; and to identify the effects of demographic variables on the Safety performance of the Indian, Bangladeshi, and Pakistani migrant workers. The effects of demographic variables on the Safety climate of the Indian, Bangladeshi, and Pakistani migrant construction workers were explored by using the Independent Sample Kruskal- Wallis and Mann-Whitney U Tests. Result: The study showed that about half of the respondents (56%) belonged to the age group of 31 to 40 years, and nearly three-quarters (78%) of them were married. Their work information showed that 75% of them are skilled workers and one-third of them (75%) work with contractors and had construction industry experience of 6 years or more. Skilled migrant construction workers have a higher commitment toward safe work than laborers. Correspondingly married construction workers, aged 30 to 50 years. and having 6-15 years of experience in the same company majorly working directly with clients, supporting 1 -2 family members, with no smoking or drinking habit have achieved a relatively higher safety climate score than the other relevant categories. Construction workers with ages less than 30 years or below, with lower education and no dependents to support, and with smoking and drinking habits have achieved relatively low safety climate score. Safety climate showed a significant positive relationship (r = 0.272, p = 0.001) with the safety performance of the Indian, Bangladeshi, and Pakistani migrant construction workers. The factor of safety climate, organizational and management safety commitment developed the strongest relationship (r = 0.339, p = 0.001) with the perceived safety climate, on the other hand, the most ignored factor with the least relationship was Workers’ Perception of Safety rules and procedures (r = 0.203, p = 0.016). Safety performance comparison among these nationalities revealed that there is an association between the country of origin and safety performance (p<0.05, χ2=6.828) and Indians showed the highest injury rates (54.4%) as compared to Pakistanis (26.3%) and Bangladeshi workers (19.3%). Conclusion: The present study suggested that there was a significant positive relationship between safety climate and the safety performance of migrant construction workers. Therefore, construction workers with less experience and lower education, aged 30 years or below, with no dependents to support, with smoking and drinking habits needs to be focused on the augmentation of their safety performance by safety awareness, relevant safety education, and training.